General Public's Attitudes Toward Disclosure of Patient Safety Incidents in Korea: Results of Disclosure of Patient Safety Incidents Survey I. Issue 1 (March 2020) - Ock, Minsu; Choi, Eun Young; Jo, Min-Woo; Lee, Sang-il
Abstract : Objectives: Many countries and organizations have promoted the disclosure of patient safety incidents (DPSI). However, reporting frequency and quality of DPSI fall short of patient and caregiver' expectations. In this study, we examined the attitudes toward DPSI of the general public representing the Korean population. Methods: Survey questions were developed based on a previous systematic review and qualitative research. Face-to-face interviews using paper-based questionnaires were conducted. We explored attitudes toward DPSI in various scenarios and opinions on methods to facilitate DPSI. Results: Almost all participants answered that it is necessary to disclose major errors (99.9%) and near misses (93.3%). A total of 96.6% (675/699) agreed that "DPSI will lead physicians to pay more attention to patient safety in the future, " and 94.1% (658/699) agreed that "DPSI will make patients and their caregivers trust the physician more." Although 79.7% (558/700) agreed that "apology law will limit patients' ability to prove physicians' negligence, " 95.4% (668/700) agreed with "I support the introduction of apology law." Moreover, 90.6% (634/700) agreed with "I support the introduction of mandatory DPSI." Conclusions: This study showed the overwhelmingly positive attitude of the public toward DPSI. The positive opinion of the public about apology law suggests the possibility of introducing the disclosure policy coupled with legislation of apology law in South Korea. Abstract : Supplemental digital content is available in the text.